Sizing of Warehouse based on Material Requirements Planning for a Polyurethane Coating Factory (2018)
The design of the warehouse is a key factor in the configuration of logistics systems, as it can facilitate the timely management of materials, intermediate and/or final products, improving the time, cost and levels of customer service. To achieve this,